Knowledge, Networks, and Knowledge Networks - Phelps, Corey; Heidl, Ralph; Wadhwa, Anu (Journal of Management, 2012)
A large and growing body of empirical research shows that social relationships and the networks these relationships constitute are influential in explaining the processes of knowledge creation, diffusion, absorption, and use. The authors refer to such networks as “knowledge networks.” They advance an understanding of knowledge networks at multiple levels by conducting a systematic review and analysis of empirical research published on this topic in leading management, psychology, sociology, and economics journals. The authors develop a comprehensive framework that organizes the knowledge networks literature, which they use to review extant empirical research within and across multiple disciplines and levels of analysis. They identify points of coherence and conflict in theoretical arguments and empirical results within and across levels and identify emerging themes and promising areas for future research.